Almost time - Schmidt, Gary D; Stickney, Elizabeth (Clarion Books, Houghton Mifflin Harcourt, 2020)
Ethan eagerly anticipates making maple syrup with his father, but it will not be time until the days are warmer, the nights shorter, and Ethan's loose tooth falls out.